2009
DOI: 10.1097/bcr.0b013e318198a2c2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers Impacting Employment After Burn Injury

Abstract: This study investigates the barriers to return to work after burn injury. The electronic records of burn survivors treated at a Regional Burn Center outpatient clinic from 2001 to 2007 were retrospectively reviewed. Inclusion criteria included employment at the time of burn injury and age 18 years or older. Documentation of barriers to return to work were reviewed and classified into eight categories. Logistic regression analysis was used to determine predictors of return to work at more than 1 year. Ordered l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 27 publications
2
28
1
Order By: Relevance
“…Significant predictors of return to work at greater than 12 months included length of hospital stay (LOS), inpatient rehabilitation, electric etiology, and burn at work (P Ͻ .05). 12 In this article, the authors reexamine the same previously published cohort to further investigate predictors of employment outcomes.…”
mentioning
confidence: 96%
“…Significant predictors of return to work at greater than 12 months included length of hospital stay (LOS), inpatient rehabilitation, electric etiology, and burn at work (P Ͻ .05). 12 In this article, the authors reexamine the same previously published cohort to further investigate predictors of employment outcomes.…”
mentioning
confidence: 96%
“…Thus far, research in this vein has tended to focus on barriers to (2)(3)(4)(5)(6) and/or facilitators of (7-10) a return to the workplace. Although this is an important milestone in the return-to-work process, it is only a step toward the achievement of a safe and sustainable employment outcome.…”
mentioning
confidence: 99%
“…15 Electrical burns also can cause significant difficulty in returning to work, 20,36 including prolonged unemployment; employment after electrical burn may also be affected negatively by WC as found in other injury populations. 36 We found significantly higher costs in claims with psychiatric diagnosis in both categories of TBSA and more days of time loss in claims with Ն10% TBSA. This does not necessarily reflect an association with psychiatric diagnosis and severity of burn (TBSA does not account for depth of burn and therefore does not equal severity; other studies have generally not found an association between severity and diagnosis such as PTSD).…”
Section: Discussionmentioning
confidence: 95%